Honeyball & Bowers' Textbook on Employment Law - Simon Honeyball (United Kingdom Oxford University Press, 2016)
Succinct in its treatment of the fundamentals, and interwoven with contextual explanation and analytical consideration of the key debates, Honeyball & Bowers' Textbook on Employment Law continues to provide readers with an accessible account of the subject. Including chapter introductions and new end-of-chapter summaries, students of employment law are guided through the intricacies, while further reading suggestions assist with independent research and essay preparation. The critical elements of individual and collective employment law are considered along with treatment of the relationship between UK and EU law, to give readers a wider view of the issues.
Keywords: Employment law; Law; (ASB-2400) Law for Business